A lignin polymer nanocomposite based electrochemical sensor for the sensitive detection of chlorogenic acid in coffee samples. Issue 3 (March 2019) - Chokkareddy, Rajasekhar; Redhi, Gan G.; Karthick, T.
Abstract: In this study, an innovative nanocomposite of multiwalled carbon nanotubes (MWCNTs), copper oxide nanoparticles (CuONPs) and lignin (LGN) polymer were successfully synthesized and used to modify the glassy carbon electrode for the determination of chlorogenic acid (CGA). Cyclic voltammetry (CV) emphasised a quasi-reversible, adsorption controlled and pH dependent electrode procedure. In cyclic voltammetry a pair of well distinct redox peaks of CGA were observed at the LGN-MWCNTs-CuONPs-GCE in 0.1 M phosphate buffer solution (PBS), at pH 2. The synthesized nanoparticles and nanocomposites were characterized by Fourier transformation infrared spectroscopy (FTIR), transmission electron microscopy (TEM) and x-ray diffraction (XRD) analyses. Differential pulse voltammetry (DPV) was applied to the anodic peak and used for the quantitative detection of CGA. Under optimal conditions, the proposed sensor showed linear responses from 5 μM to 50 μM, the linear regression equation Ipa (μA) = 2.6074 C-5.1027 (R 2 = 0.995), whilst the limit of detection (LOD) and limit of quantifications (LOQ) were found to be 0.0125 μM and 0.2631 μM respectively. The LGN-MWCNTs-CuONPs-GCE were applied to detect the CGA in real coffee samples with the recovery ranging from 97 to 106 %. The developed sensor was successfully applied for the analysis of CGA content in the coffee samples. In addition, electrophilic, nucleophilic reactions and chlorogenic acid docking studies were carried out to better understand the redox mechanisms and were supported by density functional theory calculations.